I need to prove that

$\sum_{i-is-even}^n \binom{n}{i} = \sum_{i-is-odd}^n \binom{n}{i}$

i starts from 0.

I succeeded proving this for odd n. But how to prove it for even n's?

  • 3
    $\begingroup$ Hint: Look at the binomial expansion of $(1+x)^n$ and consider $x=-1$ $\endgroup$
    – user12345
    Apr 20, 2017 at 16:48
  • $\begingroup$ Hint: Expand $\binom ni = \binom{n-1}{i-1} + \binom{n-1}i$. $\endgroup$
    – Arthur
    Apr 20, 2017 at 16:49
  • $\begingroup$ Your assertion can be rephrased as: $\sum_{k=0}^{n} (-1)^{k} \binom{n}{k} = 0$. See math.stackexchange.com/q/94514/215011 $\endgroup$
    – grand_chat
    Apr 20, 2017 at 17:16
  • $\begingroup$ If $n > 0$ !!!. $\endgroup$ Apr 24, 2017 at 2:10

1 Answer 1


We show equality by showing the difference of both sums is zero.

We obtain \begin{align*} \sum_{{i=0}\atop{i \text{ even}}}^n&\binom{n}{i}-\sum_{{i=0}\atop{i \text{ odd}}}^n\binom{n}{i}\\\ &=\sum_{{i=0}\atop{i \text{ even}}}^n\binom{n}{i}(-1)^i+\sum_{{i=0}\atop{i \text{ odd}}}^n\binom{n}{i}(-1)^i\tag{1}\\ &=\sum_{i=0}^n\binom{n}{i}(-1)^i\tag{2}\\ &=(1-1)^n\tag{3}\\ &=0 \end{align*} and the claim follows.


  • In (1) we multiply the terms with $(-1)^i$, which is $1$ if $i$ is even and $-1$ if $i$ is odd. This is just a preparation to easily merge both sums.

  • In (2) we simplify the expression by adding both sums.

  • In (3) we apply the binomial theorem.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.